Adaptasi Model Bisnis Real Estate Menggunakan Business Model Canvas: Studi Kasus Pt. Bayu Cahaya Gemilang Bogor - Cahyaputra, Muhammad Rizqy; Tricahyono, Dodie (eProceedings of Management, 2024)
In the last few decades, the property industry in Indonesia has experienced rapid growth, driven by economicgrowth, changing societal perspectives, and increasing need for commercial and residential facilities. Lifestylechanges are also influencing the growth of this industry. Despite growing rapidly, the Indonesian propertyindustry faces a number of problems, such as intense competition and a housing shortage. Additionally, changingdemand patterns caused by the popularity of e-commerce, leading to an overstock of commercial properties, aswell as frequently changing government regulations, add to the complexity of the industry. Data shows that thegrowth of the property sector will still be very volatile until 2023. This research is an adaptation of the BusinessModel Canvas of PT's real estate business. Bayu Cahaya Gemilang Bogor uses Pivot Strategy design. This isneeded by PT. Bayu Cahaya Gemilang to solve the problems that PT. Bayu Cahaya Gemilang, because there isalways a decline in income and it is still very fluctuating in terms of income in the last four years. This research uses descriptive qualitative methods with data collection techniques through interviews and documentation. Theresource persons were 5 people from internal parties at PT. Bayu Cahaya Gemilang. Based on the results ofinterviews with sources, Business Model Canvas PT. Bayu Cahaya Gemilang is quite good because it includesnine main elements. However, the problems expressed in interviews regarding the four Pivot Strategy indicat orsshow that seven elements of the Business Model Canvas have changed, namely Channels, Customer Relationships,Key Resources, Key Activities, Key Partnerships, Cost Structure, and Revenue Streams. The results of thisresearch regarding alternative strategies from the pivot strategy aspect are from the Customer Pivot Strategycategory of speed of response: adding a WhatsApp business system for service. Technology Pivot Strategyplatform category: adding promotions through the marketplace and advertising on social media such asInstagram and Tik Tok. Business Sysytem Infrastructure payment category: Added a 1 year cashback programsystem. Economics/Profitability category of cooperation agreement: Collaborating again with property agents byhaving a notary and providing sales-based commissions to property agents. Keywords-business model canvas, pivot strategy, management straegy, PT. Bayu Cahaya Gemilang